Análises morfológicas do epidídimo de ratos pós-púberes e idosos após o tratamento com doses suprafisiológicas de decanoato de nandrolona e o exercício resistido em meio aquático - Brandl, Lana (2016)
Nowadays, the search for beauty, has caused health problems associated with the use of anabolic androgenic steroid (AAS) and even strenuous exercise, and the male reproductive system is the subject of studies to be sensitive to changes in the concentration of this type of hormone; these changes may also occur with increasing age, causing changes in androgen-dependent organs, like the epididymis. This study aimed to verify if treatment with AAS associated or not to exercise, in Sprague-Dawley rats alters the morphology of the epididymis in adult rats and its chronic effects in the elderly. The training was conducted by jumping into the water, weighing overloading, being considered as resistance exercise in water. The AAS administration occurred by intramuscular injection of nandrolone decanoate (10 mg / kg / week). Epididymal samples were subjected by histological routine of hematoxylin and eosin for morphological and morphometric analysis. It was analyze all parts of the epididymis (initial segment, caput, corpus and cauda) of 56 Sprague-Dawley rats, virgins, with 13 weeks old, divided into eight groups with seven animals each: GC - adults and sedentary; GCi - elderly and sedentary; GN - adults, sedentary treated with AAS; GNi - elderly, sedentary treated with AAS; GE - adults treated with exercise; GEi - elderly treated with exercise; GNE - adults, exercise and treatment with AAS; GNEi - elderly, exercise and treatment with AAS. The results show significant changes in duct diameters; the GE was lower when compared to other groups, and the groups that were used anabolic steroids, had a larger diameter than the other, and these changes occurred mainly in the initial segments. The epithelial height in the initial segment was also considered higher in the groups that administered AAS. The elderly groups tend to return to normal, increasing the parameters of epithelial height and diameter when these were decreased, and lowering them when they were enlarged when compared with the related adult group (with common variable), except at the tail of GNEi. As the results of this study, we can conclude that both treatment in adulthood, with exercise and the use of AAS, changes morphometric and morphological parameters of the epididymis, and its chronic effects can be diminished with age.